1997
DOI: 10.1002/(sici)1520-6378(199704)22:2<96::aid-col5>3.3.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Chroma variations and perceived quality of color images of natural scenes

Abstract: DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
2
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 0 publications
3
52
2
2
Order By: Relevance
“…Overall, a methodology for the determination of perceived color-gamut volume and scaling of observer preference as a function of perceived gamut volume was established in the context of previous work in this area by Fedorovskaya et al 6 The methodology was refined and validated over a series of two experiments that measured color appearance and preference as a function of color-gamut volume in terms of psychophysical and appearance metrics. In Experiment I, the results of two different laboratories demonstrated that the effect of the perception of colorfulness is relatively strong compared with other color appearance attributes in images where the volume of display color gamut is varied.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, a methodology for the determination of perceived color-gamut volume and scaling of observer preference as a function of perceived gamut volume was established in the context of previous work in this area by Fedorovskaya et al 6 The methodology was refined and validated over a series of two experiments that measured color appearance and preference as a function of color-gamut volume in terms of psychophysical and appearance metrics. In Experiment I, the results of two different laboratories demonstrated that the effect of the perception of colorfulness is relatively strong compared with other color appearance attributes in images where the volume of display color gamut is varied.…”
Section: Resultsmentioning
confidence: 99%
“…[3][4][5] Hence, a display with a wide color gamut is an advantage in consumer markets. Although Fedorovskaya et al 6 and Shimada et al 7 investigated the color appearance and image quality when varying the chroma of images or color gamut of a display, their investigations do not correspond to the extended gamut and large-screen displays of today. The current studies of Laird and Heynderickx 8 and Hisatake et al 9 also indicate that the preferred gamut or optimal limit of chromaticities were smaller than that of the wide-gamut display from observers' preferred saturation in natural images.…”
Section: Introductionmentioning
confidence: 99%
“…However, few papers have been reported on quantitatively assessing perceived colorfulness using displays with various maximum luminances of white and various color gamuts. Fedorovskaya et al 1 examined perceived colorfulness by changing the colorfulness of images, but they did not change the maximum luminance of white. Similarly, Sakurai et al [2][3] examined the relationship between display's gamut and perceived gamut, but they did not change the maximum luminance of white.…”
Section: Objectives and Backgroundmentioning
confidence: 99%
“…Higher chroma levels are generally more attractive to the human eye. [24][25][26][27][28] Hence, when a 6500 K fluorescent lamp is used, illuminance levels higher than 500 lx are suitable for warm-colored and green flowers, considering the higher colorfulness and lower color difference. White, purple-blue, and purple flowers exhibited negligible color changes, indicating that they are less sensitive to the illuminance level.…”
Section: Experiments 1: Color Appearance Of Flowers Under 6500 K Fluormentioning
confidence: 99%